Internalisasi Nilai-nilai Piil Pesenggiri dan Islam Moderat dalam Menangkal Paham Radikal pada UKM Mahasiswa UIN Raden Intan Lampung - Lazwardi, Dedi; Amirudin, Amirudin; Nasution, Sri Purwanti; Subandi, Subandi (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research offers a solution that one of the real forms that can be done by higher education is to strengthen local cultural values, for example the Lampung area with the philosophy of Piil Pesengiri integrated with moderate Islam or Islam Rahmatan Lil a’alamin will be able to counter radical ideals among students. The purpose of this study was to determine the description of the internalization model of local cultural values (Piil Pesenggiri) and moderate Islam in counteracting radicalism in the Student Activity Unit of UIN Raden Intan Lampung. This research use desciptive qualitative approach. The conclusion in this study is the internalization process of Lampung cultural values in UKM UIN Raden Intan Lampung, among others, through the strengthening and strength of local ideology (local Wisdom) ideology such as piil pesenggiri in ulun lepung culture which consists of 5 philosophies, namely nickname adek, meet nyimah, negah nyampur, sakai sambayan and titei gemettei, integrated UKM activities are able to harmonize the existing culture in the customs of the people of Lampung (local wisdom) with Islamic values rahmatan lil allamin so that learning about Islam is also taught about the values of tolerance, the value of diversity. Culture and race, national values (ukuwah watoniyah) so that they are able to motivate the emergence of nationalism as a nation and state and love for the Indonesian homeland. Keywords: Piil Pesinggiri, Moderate Islam, Redicalism, UKMUIN Raden Intan Lampung